The Number of Biological Parents with Alcohol Use Disorder Histories and Risk to Offspring through Age 30 - Kosty, Derek B. (Addict Behav, 2019)
OBJECTIVE: We investigated associations between the number of parents with histories of alcohol use disorder (AUD) and several offspring (proband) variables through age 30: occurrence of AUD and, separately, alcohol dependence; onset age of the initial AUD episode; time to recovery from the first AUD episode; number of distinct AUD episodes; and cumulative duration of AUD across episodes. METHODS: Offspring data were collected during four assessment waves of a longitudinal epidemiological study of psychiatric disorders with a regionally representative sample. The reference sample included 730 offspring with diagnostic data from at least one parent. Offspring were assessed with semi-structured diagnostic interviews between mid-adolescence and young adulthood and parents were assessed when offspring were approximately 24 years of age. RESULTS: As the number of parents with AUD increased, offspring risk for AUD and alcohol dependence also increased. Latent growth model results indicated that offspring AUD risk trajectories increase in severity as a function of the number of parents with AUD. This pattern of results was not observed for other AUD course-related features in offspring (i.e., number of distinct episodes; months required for recovery from initial episode; cumulative duration across episodes). CONCLUSIONS: The number of parents with a history of AUD is associated with overall offspring risk for AUD and alcohol dependence and elevated AUD risk trajectories through age 30. The number of parents with AUD may be a more relevant risk factor for onset-related characteristics of AUD in offspring than for its longitudinal course.